Legal Formulation Policy for Deeds Issued by Temporary Land Deed Officials (PPATS) - Mashuri, Mashuri; Sri Darmadi, Nanang; Hafidh, Muhammad (Jurnal Konstatering, 2025)
Abstract. PPATS becomes incompetent in making all forms of real deeds compared to Notaries or PPATs who obtain their positions through legal education and internships at the BPN office or at PPAT, so that the position of Notaries and PPATs is better than PPATS, so a legal formulation is needed that can regulate the limits of PPATS's authority in carrying out duties as PPAT. The research discussion includes two things, firstly how to register deeds (transfer of land rights) registered by Temporary Land Deed Making Officers in accordance with the provisions of PP Number 24 of 1997 concerning Land Registration and how is the concept of legal formulation regulating the registration of land deeds registered by Temporary Land Deed Making Officers in the future. This study aims to analyze the registration of land transfer deeds registered by Temporary Land Deed Making Officers in accordance with the provisions of PP Number 24 of 1997 concerning Land Registration. To find the right legal formulation for Temporary Land Deed Makers (PPATS) in the future. Approach Method used by the researcher in this thesis The type of research used by the author in this thesis is normative legal research. The types and sources of data used are primary, secondary, and tertiary data sources. The data collection method is a literature study, the research data analysis method carried out by the author is prescriptive. The results of the research and discussion show that: First, the PP on Land Registration does not regulate the authority of Temporary PPAT to register land transfer deeds while the authority of Temporary PPAT is obtained from the PP on PPAT Position which gives authority to Temporary PPAT to act as PPAT. Second, PPAT in Indonesia as a whole has begun to emerge and even in some areas the quota for PPAT is full, so there is no need to worry if PPATS is abolished in the legal regulations in Indonesia because with the large number of PPATs spread across various provinces in Indonesia, it would be better to optimize the distribution of the number of PPATs in 33 provinces in Indonesia by limiting PPATs to choose their legal work area and giving authority to BPN to regulate the distribution of PPATs in areas where there are no PPATs yet.